The Impact of Conservative Society to Queer Community in Adelina Ayu’s ‘Happy Ending Machine’ - Hanifah, Nazla (Politeknik Negeri Sriwijaya, 2025)
This research explores the impact of conservative societal norms and the influence of homophobic parents on the homosexual protagonist, Shailendra, as depicted in Adelina Ayu’s Happy Ending Machine. Against the background of a society rooted in Indonesia’s traditional values, Shailendra’s journey unfolds, emphasizing the broader challenges faced by queer individuals navigating the conflict between personal authenticity and societal expectations. Using a qualitative literary analysis, this study explores the emotional and mental impact experienced by Shailendra as he struggles with societal norms, adopts a ‘closeted’ personality, and develops trust issues. The findings underscore the deep impact of conservative societal norms, depicting Shailendra’s struggles as representative of the broader challenges experienced by queer individuals in a society that refuses to accept them. In conclusion, this research advocates for societal empathy and inclusivity, encouraging the creation of an environment where diverse identities can thrive without fear of judgment or discrimination. Shailendra’s narrative in Happy Ending Machine serves as a poignant depiction of the complexities inherent in the intersection between personal identity and societal norms, highlighting the need for a more compassionate and understanding society